15x+7x+x=

Simple and best practice solution for 15x+7x+x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x+7x+x= equation:


Simplifying
15x + 7x + x = 0

Combine like terms: 15x + 7x = 22x
22x + x = 0

Combine like terms: 22x + x = 23x
23x = 0

Solving
23x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '23'.
x = 0

Simplifying
x = 0

See similar equations:

| y=-0.70(40)+122 | | 9n^2+5=59 | | 3w^2+7w=0 | | (2+x)-3x-2-(10x)=3x+3 | | y=-0.70(30)+122 | | 4.1+x=7 | | 9x^3+6x^2+12x=0 | | 7w-10w=-27 | | 2x^2+18x+326=0 | | y=-0.70(20)+122 | | K^2-18k+65=0 | | -2x-4=4x-4-10 | | -4.8+b+0.6b= | | 11x+-2=75 | | -2-4=-3+x | | 2x^2+16x+322=0 | | 12-44=5(x-2)-7 | | 5x+7y-2xy=5 | | 5(3)-2(-7)=-2 | | n^2-18=7 | | 40x+4.39=10x+6.18 | | 0.5x+15+8.2x-16.6= | | 11n=63 | | 0.69=ln(y) | | 24y-2(6-y)=6(6y+2) | | -2+x-3x=-3x+8 | | (5z+4)(6+z)=0 | | -3.5x+1.7+9.1x-0.3= | | -6x^2-45x-75=0 | | 10x+36y= | | (4y+5)(3-y)=0 | | 4y-2+46=8y+50-5y |

Equations solver categories